Unveiling the Preferred Methods in Grammar Learning: Beliefs from EFL Undergraduates - Anisah, Siti (Journal of Language and Literature Studies, 2025)
Due to its fluidity, learners’ beliefs in English language teaching (ELT) have long been a topic of discussion among scholars. This paper sheds light on what learners believe about grammar learning. This study involved forty-five undergraduate students from the English language education (ELE) department in five different universities in East Java, Indonesia. Then, using a survey design, the current investigation aims to reveal the beliefs of undergraduates concerning instructional methods they prefer while learning grammar in the classroom. Data were collected through a questionnaire covering statements representing form- and meaning-focused instruction, focus on form and focus on forms instruction, implicit and explicit instruction, deductive and inductive instruction. The questionnaire results were analyzed using descriptive statistics to facilitate the interpretation of numerical findings. Based on empirical evidence, it was found that Indonesian EFL undergraduates prefer methods that give them a central focus on grammar, such as form-focused instruction, focus on forms, explicit instruction, and deductive instruction. Furthermore, this study offers valuable insights into how teachers in higher education can effectively teach grammar to students by considering their individual learning preferences.